Anesthetic Management of Apert Syndrome: A Case Report - Koirala, Megha; Shrestha, Gentle S; Joshi, Pankaj; Parajuli, Bashu D (Journal of Institute of Medicine Nepal, 2021)
Apert syndrome is a rare autosomal dominant disease associated with abnormalities of skull, face and limbs. These patients present for different types of surgeries. To the anesthesiologists,they pose special challenge during airway management, manifesting as difficulty in bag-mask ventilation and increased incidence of airway obstruction. Here, we report a case of a child with Apert syndrome undergoing syndactyly release under general anesthesia, in whom severe bronchospasm and a failed bag-mask ventilation occurred during the emergence of anesthesia requiring re-insertion of laryngeal mask airway.